Social determinants of green technology adoption - Abdullah, Noraini; Mohd Zahari, Fadhilah (2015)
Awareness of green technology is absolutely crucial to be instilled in the people of Malaysia began when they were in school and especially among students of higher educational institutions. Social media often report that awareness of green technology among the people in this country is still lacking with the environmental concern that causes increasingly threatened and affected by human activities that are not environmentally conscious.Given the high awareness of environmental impacts among people, it can help reduce the negative effects of environmental pollution, such as global warming, the greenhouse effect and so on.This research explores the social determinants of green technology adoption. It is seen from two independent variables that is influenced from social networks and family values which is applied in everyday life. Generally, this study is made to explore the level of awareness and the significance of social determinants of green technology adoption among students in Universiti Utara Malaysia, Sintok, Kedah. The methodology in the preliminary study is expected to be used in the form of a quantitative method. Consequently, higher education institutions such as Universiti Utara Malaysia (UUM), also with a sense of responsibility and concern have taken a role in educating the campus to love, protect and respect the environment.